Use of sensors for efficient design of innovative seismic protection techniques for monuments - Chrysostomou, Christis; Votsis, Renos; Kyriakides, Nicholas; Stassis, Andreas (My University, 2010)
One of the most difficult problems in the design of seismic protection for monuments is the establishment of their in-situ properties in order to be able to use them for an as accurate as possible model of the structure. In addition, any retrofitting method that will be used should be inconspicuous, and it should neither violate its form, nor change its structural behavior. In this work the in-situ dynamic characteristics of an aqueduct are obtained using accelerometers to record the response of the structure to ambient vibrations, and hence finite element models which are updated based on those measurements are developed. The effectiveness of the use of shape-memory-alloy wire-dampers for the protection of the monument from earthquakes is evaluated through their application on the monument and in-situ measurement of the changes in its dynamic characteristics.
Keywords: Structural design; Maintainability (Engineering); Seismology